Endoscopic or Conservative Management of Iatrogenic Duodenal Perforations Caused by Long Plastic Biliary Stent Distal Migration - Thapa, Namisha (ACG Case Rep J, 2020)
Plastic biliary stents are associated with rare but potentially life-threatening distal stent migration. We present 4 patient cases with distal migration, whereas the proximal aspect remained in the bile duct. Time to stent migration ranged from 1 week to 2 months. Stent migration caused contralateral duodenal wall perforation; 2 underwent endoscopic over-the-scope clip placement for defect closure. All required previous stent removal and stent exchange. This case series highlights that proximal stricture and longer stents have higher migration risk, also shown in the literature. We also show that duodenal perforation can successfully be managed endoscopically with an over-the-scope clip.